Diagnóstico de los parámetros físicos del cacao en centros de acopio en la zona de influencia de los valles Carrizal-Chone. - García Cedeño, Luigi Armando (2017)
This research was carried out from December 2016 to March 2017 at Escuela Superior Politécnica Agropecuaria de Manabí “Manuel Félix López” and at Fortaleza del Valle Corporation in order to determine the physical quality of the cocoa beans which are produced in the area of influence of the Carrizal-Chone valleys, to establish their quality and thus to know if they meet the parameters established by INEN 173 and 176 for international marketing. For the processing of the parameters a database was established where the evaluated variables were recorded: percentage of fermentation, percentage of testa and cotyledon, humidity, seed index and percentage of impurities. The results indicate that the collected samples of cocoa at the collection centers of the Carrizal-Chone valley influence zone do not meet the parameters established by the INEN-176 standard, this is due to the fact that the grains do not receive the proper post-harvest management by the producer and are deliver like that to the collection centers.